2014
DOI: 10.1002/pc.23063
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and analysis of injection‐molded nanocomposites of recycled high‐density polyethylene incorporated with graphene nanoflakes

Abstract: Recycled high-density polyethylene (HDPE) was incorporated with graphene nanoflakes in a solvent at different concentrations (0, 1, 2, 4, and 8 wt%), and then the mechanical, thermal, electrical, and surface hydrophobic properties of the resultant nanocomposites were determined using universal tensile testing, thermal comparative, capacitance bridge, and goniometer techniques, respectively. The test results revealed that the mechanical, thermal, and dielectric properties of the polymer matrix nanocomposites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Many reports are available related to the incorporation of graphene into the HDPE matrix using solution blending techniques. Asmatulu et al 74 prepared recycled HDPE/graphene nanoake composites by the solution blending method using toluene as the solvent. The maximum of 8 wt% of graphene was incorporated to get improvement in the mechanical, thermal, and dielectric properties of the polymer nanocomposites as a function of graphene concentration.…”
Section: Solution Blendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports are available related to the incorporation of graphene into the HDPE matrix using solution blending techniques. Asmatulu et al 74 prepared recycled HDPE/graphene nanoake composites by the solution blending method using toluene as the solvent. The maximum of 8 wt% of graphene was incorporated to get improvement in the mechanical, thermal, and dielectric properties of the polymer nanocomposites as a function of graphene concentration.…”
Section: Solution Blendingmentioning
confidence: 99%
“…They found that an increase of 118% in storage modulus of nanocomposites at 8 wt% of DA-G (from 134 MPa to 293 MPa at 50 C) is because graphene acts as a reinforcing ller, which signicantly decreases the chain mobility of the LLDPE matrix. Asmatulu et al 74 reported the improved mechanical properties of the HDPE/graphene composite. The ultimate tensile strength increased by 56% (at 4 wt% graphene) and >100% in tensile modulus (from 200 to 450 MPa) at 1 wt% graphene loading, which could be attributed to the thickness of the graphene sheet (0.35-1 nm) leading to high surface area and increased load transfer sites between the polymer matrix and ller.…”
Section: Mechanical Properties Of Polyolen/graphene Compositesmentioning
confidence: 99%
“…The contribution of poisson's effect also plays an important role [23]. The resistivity and changes in dimension may be related to the fiber buckling, delamination, cracks, voids, internal defects and secondary phase of the composites [26][27][28][29][30]. However, the relation between dimensional changes and resistivity changes because of the loading and unloading requires more research.…”
Section: Figurementioning
confidence: 99%
“…Industrial changes and technological challenges have been forcing many scientists and researchers on developing new and functional materials for different harsh conditions [5][6][7][8][9][10][11][12][13][14]. In the present study, silicon carbide (SiC) whiskers and chopped carbon fibers were chosen as the fill materials to study as they are both highly abrasive and conduct heat very well.…”
Section: Introductionmentioning
confidence: 99%